Integrating LiDAR-derived DEM, rainfall radar data, and SAR imagery for 2D HEC-RAS modelling to assess the severity of pluvial flash floods induced by Storm Boris in SE Romania - Alin Mihu-Pintilie; Andrei Urzică; Cristian Constantin Stoleriu; Claudiu Ionut Pricop (Geomatics, Natural Hazards & Risk)
In this study, we aimed to assess the severity of 13 to 14 September, 2024, pluvial flash floods event induced by Storm Boris in SE Romania, by a combination of two watersheds (W1 and W2) and 14 settlements scale assessment and weather radar rainfall data and calibrated hydrological datasets, available SAR imagery and 2D HEC-RAS modelling on high-density LiDAR-data. To achieve this, multiple 2D flash flood parameters derived from HEC-RAS data processing, including flash flood extent, depth and velocity, were computed. To validate the hydraulic models, SAR imagery captured after the flash flood event and official flood hazard maps computed for 1,000-year return periods were used. The results indicate that SAR imagery partially captured the flood extent, while official flood hazard maps suggest that the flash flood event has a recurrence interval of 1,000 years. The most affected settlements were located in the central-upper parts of the W1 and the central-lower parts of W2 (7 casualties, > 5,000 houses directly affected, 60.2 km of roads impacted). Overall, this study offers a complete perspective of pluvial flash flood severity and contributes to improvement of official flood hazard maps by recalibrating the discharge data used for return period computation.